R‐CHOP versus dose‐adjusted R‐EPOCH in frontline management of primary mediastinal B‐cell lymphoma: a multi‐centre analysis. (19th December 2017) - Shah, Nirav N.; Szabo, Aniko; Huntington, Scott F.; Epperla, Narendranath; Reddy, Nishitha; Ganguly, Siddhartha; Vose, Julie; Obiozor, Cynthia; Faruqi, Fahad; Kovach, Alexandra E.; Costa, Luciano J.; Xavier, Ana C.; et al.
Summary: Primary mediastinal (thymic) large B‐cell lymphoma (PMBCL) is an uncommon subtype of non‐Hodgkin lymphoma (NHL) that presents with a mediastinal mass and has unique clinicopathological features. Historically, patients with PMBCL were treated with R‐CHOP (rituximab, cyclophosphamide, doxorubicin, vincristine, prednisone) chemotherapy ± involved field radiation. Since a phase II trial, published in April 2013, demonstrated excellent results using dose‐adjusted (DA) R‐EPOCH (rituximab, etoposide, prednisone, vincristine, cyclophosphamide, doxorubicin), this treatment has gained popularity. We performed a retrospective, multicentre analysis of patients aged ≥18 years with PMBCL since January 2011. Patients were stratified by frontline regimen, R‐CHOP versus DA‐R‐EPOCH. 132 patients were identified from 11 contributing centres (56 R‐CHOP and 76 DA‐R‐EPOCH). The primary outcome was overall survival. Secondary outcomes included progression‐free survival, complete response (CR) rate, and rates of treatment‐related complications. Demographic characteristics were similar in both groups. DA‐R‐EPOCH use increased after April 2013 (79% vs. 45%, P < 0·001), and there was less radiation use after DA‐R‐EPOCH (13% vs. 59%, P < 0·001). While CR rates were higher with DA‐R‐EPOCH (84% vs. 70%, P = 0·046), these patients were more likely to experience treatment‐related toxicities. At 2 years, 89% of R‐CHOP patients and 91% of DA‐R‐EPOCH patients were alive. To our knowledge, this represents the largest series comparing outcomes of R‐CHOP to DA‐R‐EPOCH for PMBCL.